THE EFFECT OF EMOTIONAL INTELLIGENCE AND TEACHER SELF-EFFICACY ON CLASS MANAGEMENT MODERATED WITH TRANSFORMATIONAL LEADERSHIP STYLE - Rubiyatun Rubiyatun; Fauzan Fauzan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to examine and analyze the effect of emotional intelligence and teacher self-efficacy on classroom management moderated by transformational leadership style at SMA Negeri sub rayon 03 Semarang city. This type of research is explanatory research because this research explains the influence between variables and tests the research hypotheses that have been formulated. The population in this study were teachers of SMA Negeri sub rayon 03 Semarang city which were taken as a sample of 151 people. The analysis technique uses multiple linear analysis multiple linear regression analysis. The results showed that emotional intelligence has an effect on classroom management, teacher self-efficacy has a negative effect on classroom management, transformational leadership style does not moderate the effect of emotional intelligence on classroom management, transformational leadership style moderates the effect of teacher self-efficacy on classroom management. Keywords: Emotional intelligence, teacher self-efficacy, classroom management, and transformational leadership style.